4CPS-403 Chronic kidney disease patients and polypharmacy: how to optimise and simplify prescriptions?. (14th March 2021) - Masucci, S; Soragna, G; Cavalleris, G; Parola, B; Vitale, C; Gasco, A
Abstract : Background and importance: Patients with chronic kidney disease (CKD) are often characterised by the concomitance of multimorbidity, which could cause complex drug prescriptions that lead to a higher risk of incorrect administration and serious drug–drug interactions (DDIs) and potentially inappropriate medications (PIMs). According to national recommendation No17 of the national health system (NHS), these patients need appropriate attention: a multidisciplinary team (clinical pharmacists–clinician–nurse) should systematically re-evaluate pharmacological therapies to simplify/harmonise treatments and increase patient adherence. Aim and objectives: The aim of this study was to improve a method to analyse pharmacological therapies, identify incorrect prescriptions and simplify therapies. Material and methods: The chosen method requires that the clinical pharmacist in the nephrological team collaborates to analyse 231 therapies of patients, is in charge of the advanced renal disease clinic, using an already identified information and communication technology (ICT) tool. 1 Drugs, classified by anatomical therapeutic chemical class (ATC), and dosage units (DU) were counted and DDIs were investigated. PIMs and dangerous drugs were identified by Beers criteria and STOPP criteria. Results: 2311 drugs and 2695 DU were counted. Each patient was receiving 10±3.1 different medicines, corresponding to 12.1±8.1 DU/day. 91% of patients were taking 5 or more DU/day and 59.3% at least 10. Stratifying drugs by ATC class identified the following: 644 prescriptions for C02-antihypertensives class, 184 for M04-gout preparations, 135 for C10-lipid modifying agents and 218 for B03-antianaemic preparations. 64% of patients (139) used gastroprotectors, especially proton pump inhibitors (PPIs). 3 DDIs, of 289 detected, were considered contraindicated and potentially serious, and were due to antipsychotic drugs. Drugs most responsible for DDIs were: cardioaspirin, PPIs, angiotensin receptor blockers and diuretics. 975 (4.2±2.2 per patient) and 571 (2.4±1.7 per patient) inappropriate drugs were identified according to STOPP criteria and Beers criteria, respectively. Conclusion and relevance: Polypharmacy is associated with a high incidence of DDIs and an increased risk of mortality and hospitalisation. The use of the ICT tool and the clinical pharmacist who bring their contribution in terms of pharmacological and pharmacokinetic knowledge have significantly contributed to the improvement in prescriptive appropriateness and minimised the risk of adverse events. References and/or acknowledgements: Critical analysis of the information and communication technologies' (ICT) tools most used in clinical practice by the pharmacist. Masucci S, Cerutti E, Riba M, Gasco AL (EAHP Congress 2019). Conflict of interest: No conflict of interest